2017
DOI: 10.12691/jfnr-5-12-6
|View full text |Cite
|
Sign up to set email alerts
|

Amaranth Protein Improves Lipid Profile and Insulin Resistance in a Diet-induced Obese Mice Model

Abstract: Amaranth has been claimed as functional food, but its function on obesity-related disorder is not fully known. The aim of this study was to analyse the effect of amaranth protein intake on blood lipids profile and insulin resistance in diet-induced obese mice. The effect of soybean protein was also analysed for comparative purposes. C57BL-6 mice were fed for eight weeks with regular or high fat diet. Amaranth or soybean protein isolates (10 mg/kg) were supplied via oral administration. Changes in body weight, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 39 publications
1
2
0
Order By: Relevance
“…It has stated that Ruminoccocaceae induced expression of genes involved in infl ammation process, such as Angpl4, in diet-induced obese mice [Ravussin et al, 2012]. These bacteria have been also observed in leptin--resistant obese and diabetic mice; this correlates with a previous work, which showed that mice fed with SOY protein tended to have insulin resistance [Escobedo-Moratilla et al, 2017]. The Lachnospiraceae family showed the same abundance levels in mice fed with Ctrl-and AMA diets but in caecal digesta of mice fed with SOY-diets an increase in abundance was observed ( Figure 4B).…”
Section: Sequence Analysis Of the Caecum Bacteria Populationsupporting
confidence: 79%
See 1 more Smart Citation
“…It has stated that Ruminoccocaceae induced expression of genes involved in infl ammation process, such as Angpl4, in diet-induced obese mice [Ravussin et al, 2012]. These bacteria have been also observed in leptin--resistant obese and diabetic mice; this correlates with a previous work, which showed that mice fed with SOY protein tended to have insulin resistance [Escobedo-Moratilla et al, 2017]. The Lachnospiraceae family showed the same abundance levels in mice fed with Ctrl-and AMA diets but in caecal digesta of mice fed with SOY-diets an increase in abundance was observed ( Figure 4B).…”
Section: Sequence Analysis Of the Caecum Bacteria Populationsupporting
confidence: 79%
“…The food consumption and mice weight were recorded every week. Protein isolates from amaranth and soybean, with a purity of 76.5% and 85.5%, respectively, were obtained as described elsewhere [Escobedo-Moratilla et al, 2017]. Amaranth or soybean protein was administered once daily using a stainless steel oral gavage at a dose of 10 mg protein/kg BW (body weight).…”
Section: Animals and Dietsmentioning
confidence: 99%
“…Major antioxidants in amaranth are not in the lipid part because, after fat extraction, the antioxidant value remained the same [66]. Some other researchers also reported that amaranth may act as a nutraceutical therapy in type 2 diabetes as it stimulates insulin secretion, as well as in obesity health improvements [67][68][69][70]. Unprocessed and extruded amaranth flours were found to be good sources of peptides with potential biological activity, such as ACEinhibitor and dipeptidyl peptidase IV inhibitor, thereby preventing chronic diseases [71,72].…”
Section: Minerals Vitamins and Other Bioactive Compoundsmentioning
confidence: 99%